The pipe-group architecture real-time active vision - McLauchlan, P; Reid, I; Fairley, S; Murray, D (1997)
This paper describes a vision processing architecture which, together with a robotic camera platform and control subsystem, comprise a multi-processor real-time system for research into active vision. Experimentation in time-critical aspects of the active vision paradigm over several years has demonstrated the flexibility of 'pipe-groups' used as the building block in the system. The design of the entire system is overviewed, and the design of pipe-groups and their software is described in more detail. An active method of determining the exact processing latency, required for stable control, is explained. The paper illustrates the use of the pipe-group processing architecture and its real-time processing capabilities, with an example of active stereo tracking and structure recovery using the method of affine tranfer. © 1997 Academic Press Limited.